2017
DOI: 10.1097/mib.0000000000001129
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Barrier Disruption in Ileal Pouchitis After Ileal Pouch-Anal Anastomosis in a Rat Model

Abstract: The intestinal barrier was disrupted in this rat model of pouchitis. Increased proinflammatory and decreased anti-inflammatory factors aggravated the intestinal barrier damage. Antibiotics may ameliorate this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In turn, intestinal barrier dysfunction may lead to the extension of the local small intestinal inflammatory response to a more generalized systemic response; thereby inhibiting recovery in patients with this disease . Indeed, GB dysfunction has been shown to be involved in many diseases, including ileal pouchitis, nonalcoholic steatohepatitis, and heart failure . A study by Snoek et al .…”
Section: Introductionmentioning
confidence: 99%
“…In turn, intestinal barrier dysfunction may lead to the extension of the local small intestinal inflammatory response to a more generalized systemic response; thereby inhibiting recovery in patients with this disease . Indeed, GB dysfunction has been shown to be involved in many diseases, including ileal pouchitis, nonalcoholic steatohepatitis, and heart failure . A study by Snoek et al .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical barrier, formed by neighboring epithelial cells, excludes microbial pathogen-associated molecular patterns, toxins, and foreign antigens [ 73 ]. TJ proteins, such as ZO-1 and OCLN, are essential components of the intestinal mechanical barrier [ 74 ]. Previous studies have reported decreased expression of TJ proteins in DSS-induced colitis [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a part of the intestinal immune system, the intestinal barrier is an effective protective barrier to prevent pathogenic microorganisms . More and more studies have shown that puerarin and tryptophan or its metabolites participate in maintaining intestinal homeostasis. , Studies have shown that DSS can effectively cause severe intestinal barrier damage and IBD. Therefore, DSS was used to build an intestinal barrier injury model in rats in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, mucin decreased significantly in the DSS group, suggesting that DSS just promoted the expression of VAMP8. It is well-known that DSS destroys the integrity of intestinal epithelial cells and increases intestinal permeability . Furthermore, VAMP8 is a protein associated with the cell membrane and involved in the formation of vesicles and the secretion of mucin .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation